Evaluation of the dentists? knowledge on medical urgency and emergency - Tássia Carina STAFUZZA; Cleide Felício Carvalho CARRARA; Fernanda Veronese OLIVEIRA; Carlos Ferreira SANTOS; Thais Marchini OLIVEIRA (Sociedade Brasileira de Pesquisa Odontológica, 2014)
This study aimed at evaluating how well dentists understand medical emergency/urgency procedures and issues during dental treatment at a hospital specialized in cleft lip and palate. It comprised a hundred dentists from the Hospital for Rehabilitation of Craniofacial Anomalies, University of São Paulo (HRAC/USP), Brazil, from different dental specialties. A questionnaire was applied to evaluate their knowledge of medical emergencies/urgencies from June through September 2011. The questionnaire was anonymous, confidential and constructed with closed questions and either yes-no or multiple-choice responses. Results showed that most professionals (87%) were trained in basic life support (BLS), but only 43% considered themselves capable of providing first aid and performing the necessary maneuvers. Most participants (94%) claimed that they knew the difference between medical urgencies and emergencies, and 69% had BLS training in their undergraduate courses, as opposed to 37%, during their specialization. Some participants (23%) mentioned that they had received knowledge of the subject during extracurricular courses and/or graduate courses (12%). Only 9% had not been educated on the subject; however, all participants showed interest in attending a course in BLS. In regard to assessing training that dentists who attended BLS courses received, 49% were satisfied and 42% were dissatisfied. Results of the present study emphasize that dentists from HRAC/USP have little knowledge about BLS procedures to perform them. Dentists must gain adequate education and training to minimize possible technical, ethical and legal problems associated with dental practice. It is necessary to improve both knowledge and practice in order to become well-qualified practitioners.